2012
DOI: 10.4103/2229-5186.99587
|View full text |Cite
|
Sign up to set email alerts
|

Trace element structure of the most widespread plants of genus PulmonariaFNx01

Abstract: Aim:The aim of this work was a comparative research of trace element structure of various organs of three Pulmonaria species. Materials and Methods: The aerial parts of the most widespread plants of genus Pulmonaria such as Pulmonaria officinalis L., Pulmonaria obscura Dumort. and Pulmonaria mollis Wulf. ex Hornem., which were collected in ending of flowering and were used as the research objects. The amount of trace elements (B, K, and Ti) was determined by means of mass spectroscopy with inductively coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The PMEFS restored the level of hemoglobin in the rats in 8-9 days in a similar manner to the synthetic drug (Table 1) [27]. The rats with and without PMERL treatment were able to restore the level of hemoglobin in 20 and 25 days, respectively.…”
Section: Anti-anemic Activitysupporting
confidence: 54%
See 3 more Smart Citations
“…The PMEFS restored the level of hemoglobin in the rats in 8-9 days in a similar manner to the synthetic drug (Table 1) [27]. The rats with and without PMERL treatment were able to restore the level of hemoglobin in 20 and 25 days, respectively.…”
Section: Anti-anemic Activitysupporting
confidence: 54%
“…The data clustering showed that the floral shoots and rosellate leaves have significantly different statuses of trace elements. The highest Mg and Fe content was found to be present in P. officinalis and P. mollis, respectively [27].…”
Section: Phytochemicals Present In Pulmonariamentioning
confidence: 91%
See 2 more Smart Citations